Big Cities's Challenge to Christian Identity - Leonardus Samosir (Journal of Asian Orientation in Theology, 2019)
Identity brings about positive values and demands commitment, but also potentially spreads seeds of conflict. Learning from identity as dynamically moving borders, from the phenomena multiple identity, and from discovering the meaning of religion, it is suggested, that Christianity views the so-called shaded-in area or convergent area as a place for mutual enrichment, deepening Christianity as orientation, bringing about solidarity, and learning from another views to face the complex reality of the world.